Glia of the human retina. Issue 4 (3rd December 2019) - Reichenbach, Andreas; Bringmann, Andreas
Abstract: The human retina contains three types of glial cells: microglia and two types of macroglia, astrocytes and Müller cells. Macroglia provide homeostatic and metabolic support to photoreceptors and neurons required for neuronal activity. The fovea, the site of the sharpest vision which is astrocyte‐ and microglia‐free, contains two populations of Müller glia: cells which form the Müller cell cone in the foveola and z‐shaped Müller cells of the foveal walls. Both populations are characterized by morphological and functional differences. Müller cells of the foveola do not support the activity of photoreceptors and neurons, but provide the structural stability of the foveal tissue and improve the light transmission through the tissue to the photoreceptors. This article gives overviews of the glia of the human retina and the structure and function of both Müller cell types in the fovea, and describes the contributions of astrocytes and Müller cells to the ontogenetic development of the fovea. Abstract : The human retina contains microglia, astrocytes, and Müller glia. The fovea contains two populations of Müller glia which differ in structure and function. Astrocytes and Müller glia contribute to the development of the fovea.